Probabilistic polling MAC protocol with unslotted CSMA for wireless sensor networks (WSNs) - Ur Rehman, M. (IEEE Computer Society, 2014)
Wireless sensor networks (WSNs) may lead to high traffic in network when nodes detect an event and become active to send the data to the sink. Therefore, traffic adaptive medium access control (MAC) protocol for WSNs, with a more strict collision avoidance technique, can help in resolving the issue of collision by allowing less number of sensor nodes to send the data on the shared wireless channel. Probabilistic polling is a receiver-initiated MAC protocol proposed for energy harvesting wireless sensor networks (EH-WSNs), with a channel access mechanism known as contention probability. In this mechanism the receiver sets a pre-condition for the nodes who want to relay their packets to the receiver. Node that satisfies the condition can send their data packets. In this paper, the performance of probabilistic polling protocol for battery powered wireless sensor networks (BP-WSNs) is studied instead of EH-WSNs. Also unslotted CSMA probabilistic polling (UCSMA probabilistic polling) protocol is proposed that uses the contention probability along with un-slotted CSMA/CA as channel access mechanism. The simulation results show that UCSMA probabilistic polling protocol can improve the network performance in term of high throughput and fairness. Â© 2014 IEEE.